Identification of phenolic compounds in Syzygium aromaticum (clove) using HPLC technique and evaluation of their antioxidant activity. (Journal of the College of Basic Education, 2026)
The objective of the experiment was to identify the phenolic compounds in Syzygium aromatic (clove) and to assess their antioxidant activity .maples of dried flower buds were collected. The grinding and extraction were done through the use of cold maceration with ethanol. The phenolic compounds were later identified and separated using HPLC device. According to the study, eugenol was found to be at a maximum concentration of 5.66 mg/ml with the minimum concentration of ferulic acid (0.95 mg/ml). The extract also contained gallic acid and caffeic acid as confirmed by their retention time in the HPLC chromatogram.Using three replications of each concentration (25, 50, 100, and 200 µg/ml), the antioxidant activity was firstly checked by DPPH test. On all replicates, the inhibition percentage and standard deviation of each compound were calculated and compared. Results indicate that inhibition percentage obtained at 200µg/ml of eugenol (77%) and 25µg/ml of ferulic acid (21%) were maximum and minimum respectively. Based on their IC₅₀ values, eugenol is very active even at a low concentration (44µg/mL). The ferulic acid (139 µg/mL) showed weak activity similar to those at very high doses.